1997
DOI: 10.1007/s002130050378
|View full text |Cite
|
Sign up to set email alerts
|

Previous treatment as a confounding variable in studies with novel antipsychotics: two cases of high dopamine-2 receptor occupancy with quetiapine

Abstract: Previous treatment can be a confounding variable in studies with novel antipsychotics. Quetiapine is a new antipsychotic substance with a low affinity for dopamine-2 (D2) receptors. Preliminary SPECT and PET investigations revealed only a low striatal D2 receptor occupancy rate. However, we present two cases of high striatal D2 receptor occupancy (51% and 71%) measured with 123I IBZM SPECT during quetiapine monotherapy. Both patients had previously received continuous treatment with typical neuroleptics. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 10 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…One of the most important confounding variable is premedication with typical neuroleptics and speciÞcally with depot formulations. As already previously shown, pretreatment with depot-neuroleptics with a pause for as long as 3 months is associated with higher striatal D 2 receptor occupancy rates (Harasko-van der Meer et al 1993;Tauscher et al 1997). We were also able to detect this phenomenon during sertindole treatment in two of our patients who were pretreated with depot medication.…”
Section: Discussionsupporting
confidence: 69%
“…One of the most important confounding variable is premedication with typical neuroleptics and speciÞcally with depot formulations. As already previously shown, pretreatment with depot-neuroleptics with a pause for as long as 3 months is associated with higher striatal D 2 receptor occupancy rates (Harasko-van der Meer et al 1993;Tauscher et al 1997). We were also able to detect this phenomenon during sertindole treatment in two of our patients who were pretreated with depot medication.…”
Section: Discussionsupporting
confidence: 69%
“…Quetiapine (QT) acts as antagonist at the DA D2 receptor, as well as at the serotonin 2A (5-HT2A) receptor (dose-dependent, besides additional effects at the H1 and other 5-HT and adrenergic receptors). Specifically, QT is characterized by a high affinity for the 5-HT2A receptor and a fast dissociation rate (and low affinity) for the DA D2 receptor (Kessler et al, 2006), although it has also been shown that QT can have a high (striatal) DA D2 receptor occupancy in some cases (Tauscher et al, 1997; Pavics et al, 2004). Based on these pharmacological targets, QT is used to treat patients with schizophrenia, bipolar disorder, autism, and depression (Wen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This persistence of haloperidol in the brain may explain the relatively low relapse rate in patients withdrawn from depot neuroleptic treatment compared with those withdrawn from oral treatment [51]. It also suggests that previous treatment can be a confounding variable in studies with novel antipsychotics, a phenomenon which was actually observed in SPECT studies of the brain [52]. It has been suggested that a minimum washout period of 6 months should be required in controlled clinical trials of novel antipsychotic drugs [51].…”
Section: Classical Neurolepticsmentioning
confidence: 99%